Case Report: Non-ossifying fibromas with pathologic fractures in a patient with NONO-associated X-linked syndromic intellectual developmental disorder - Writzl, Karin; Mavčič, Blaž; Maver, Aleš; Hodžić, Alenka; Peterlin, Borut (Frontiers in Genetics, 2023)
The NONO gene encodes a nuclear protein involved in transcriptional regulation, RNA synthesis and DNA repair. Hemizygous loss-of function, de novo or maternally inherited variants in NONO have been associated with an X-linked syndromic intellectual developmental disorder-34 (OMIM # 300967), characterized by developmental delay, intellectual disability, hypotonia, macrocephaly, elongated face, structural abnormalities of corpus callosum and/or cerebellum, congenital heart defect and left ventricular non-compaction cardiomyopathy. Few patients have been described in the literature and the phenotype data are limited. We report a 17-year-old boy with dolihocephaly, elongated face, strabismus, speech and motor delay, intellectual disability, congenital heart defect (ASD, VSD and Ebstein’s anomaly), left ventricular non-compaction cardiomyopathy, bilateral inguinal hernia and cryptorchidism. Additional features included recurrent fractures due to multiple non-ossifying fibromas, thrombocytopenia, and renal anomalies. Exome sequencing revealed a de novo pathogenic variant (NM_001145408.2: c.348+2_ 348+15del) in intron 5 of the NONO gene. Renal anomalies and thrombocytopenia have been rarely reported in patients with NONO - X-linked intellectual disability syndrome, while recurrent fractures due to multiple non-ossifying fibromas have not previously been associated with this syndrome. The phenotypic spectrum of NONO - X-linked intellectual disability syndrome may be broader than currently known.